Management matters: what do we need to know about the motivation and job satisfaction of humanitarian logisticians? - Jana Abikova (Journal of Humanitarian Logistics and Supply Chain Management, 2025)
Purpose – This study delineates the factors impacting the motivation and job satisfaction of humanitarian logisticians. This study aims to explore their motivations for entering the sector and the reasons for persisting despite the challenges. Design/methodology/approach – Using an exploratory research design, data were gathered through online semi-structured questionnaires distributed to international and national non-governmental organisations (NGOs), UN agencies, the International Federation of Red Cross and Red Crescent Societies, the logistics cluster and the Humanitarian Logistics Association. Findings – This study reveals that humanitarian organisations, along with their policies, culture and practices, significantly influence staff well-being. Altruistic motives drive logisticians to support those in need, aligning with their moral standards. However, job satisfaction declines due to issues such as management practices, unfairness, bureaucracy and other factors affecting work-life balance. Practical implications – These findings offer insights for humanitarian organisations to address the challenges faced by logisticians and enhance their well-being. Understanding the issues before, during and after deployment is crucial for organisational focus. Representatives from some NGOs expressed optimism about the usefulness of this data during the collection process. Originality/value – This research pioneers an examination of the motivation and satisfaction of humanitarian logisticians, contributing to the existing body of knowledge on human resources in the non-profit sector.